Nutrition and Exercise in a Case of Carnitine Palmitoyl-Transferase II Deficiency - Parimbelli, Mauro; Pezzotti, Elena; Negro, Massimo; Calanni, Luca; Allemano, Silvia; Bernardi, Marco; Berardinelli, Angela; D’Antona, Giuseppe (Frontiers in Physiology, 2021)
In the mild subtype of inherited carnitine palmitoyltransferase II (CPTII) deficiency, muscular mitochondrial fatty acid β-oxidation is impaired. In this condition, interventions involve daily dietary restriction of fats and increase of carbohydrates, whereas physical exercise is commonly contraindicated due to the risk of muscle pain and rhabdomyolysis. We present the case of a 14-year-old female with CPTII deficiency who underwent a 1-h session of unsupervised exercise training for 6 months, 3 days per week, including interval and resistance exercises, after diet assessment and correction. Before and after intervention, the resting metabolic rate (RMR) and respiratory quotient (RQ) were measured by indirect calorimetry, and a cardiopulmonary exercise test (CPET, 10 W/30 s to exhaustion) was performed. Interval training consisted of a 1 min run and a 5 min walk (for 15 min progressively increased to 30 min). During these efforts, the heart rate was maintained over 70% HR max corresponding to respiratory exchange ratio (RER) of 0.98. Resistance training included upper/lower split workouts (3 sets of 8 repetitions each, with 2 min rest between sets). Blood CK was checked before and 36 h after two training sessions chosen randomly without significant difference. After training, RMR increased (+8.1%) and RQ lowered into the physiological range (from 1.0 to 0.85). CPET highlighted an increase of peak power output (+16.7%), aerobic performance (VO2 peak, 8.3%) and anaerobic threshold (+5.7%), oxygen pulse (+4.5%) and a much longer isocapnic buffering duration (+335%). No muscle pain or rhabdomyolysis was reported. Results from our study highlight that training based on short-duration high-intensity exercise improves overall metabolism and aerobic fitness, thus being feasible, at least in a case of CPTII deficiency.